MASSIE’S DISCRIMINATION ON CLAIRE AS SEEN IN LIZ TIGELAAR’S THE CLIQUE MOVIE SCRIPT - Handoko, Putut; Saputri, Hanida Fadhilatul Eka (Faculty of Letters, Dr. Soetomo University, 2018)
The thesis writer focuses on the analysis of Massie?s discrimination on Claire as seen In Liz Tigelaar?s The Clique Movie Script. The topic discrimination is chosen because it is important to find out of the proofs, the causal factors, and the effects of Massie?s discrimination on Claire. The thesis writer applies the concept of discrimination, the types of discrimination, the causes of discrimination, the effect of discrimination, and she also applies a qualitative research. The finding shows that the proofs of Massie?s discrimination on Claire are a part of the social psychology harmful actions toward other, unjustifiable negative behavior towards a group or its members, leads the group that feels discriminated often live under ambivalent way of life. The second finding is the causal factor of Massie?s discrimination on Claire is feeling superiority against the rest. The last finding is the effects of Massie?s Discrimination on Claire. First, the effect on Claire is hidden her discrimination to her mom. The second effect on her friend is Layne angry to her. The last effect on Massie is she feels uncomfortable in her own house.Key Word: Discrimination